Finding the Approximate Solution to a Nonlinear Equation in One Variable Using Integration - Hana louka, (AlQalam Journal of Medical and Applied Sciences, 2024)
The research focuses on applying the solution method using integration to find approximate roots of a nonlinear equation. This is done by finding the integral of a function and then applying the steps of the numerical method, which facilitates finding the approximate solution to the nonlinear equation in a short amount of time. The results showed that using this method to compute the numerical solution of the nonlinear equation yields highly accurate results, with the degree of proximity to the actual values being the best. Additionally, it is an easy and quick method for calculations and plays a significant role in finding approximate solutions to higher-order nonlinear equations. When comparing the number of iterations required to find the solution using this method with other methods, the number of iterations is reduced compared to other numerical methods. However, the equality of the real roots with the approximate roots does not mean that this numerical method used to find the root is 100% accurate, as the calculated results in the previous examples were approximated to four and eight decimal places after the decimal point. يهدف موضوع البحث في تطبيق طريقة الحل باستخدام التكامل لإيجاد الجذور التقريبية للمعادلة الغير خطية، ويتم ذلك عن طريق إيجاد تكامل دالة ومن ثم تطبيق خطوات الطريقة العددية والتي تسهل إيجاد الحل التقريبي للمعادلة الغير خطية في زمن قليل. أظهرت النتائج أن استخدام هذه الطريقة لحساب الحل العددي للمعادلة الغير خطية تكون النتائج دقيقة جدًا ومدى تقاربها من القيم الحقيقية هي الأفضل، بالإضافة لكونها طريقة سهلة وسريعة في الحساب ولها دور كبير في إيجاد الحل التقريبي للمعادلات الغير خطية من الدرجات العليا، وبمقارنة عدد التكرارات لإيجاد الحل بهذه الطريقة مع الطرق الأخرى سنجد أن عدد التكرارات يتقلص مقارنة مع الطرق العددية الأخرى. ولكن تساوي الجذور الحقيقية مع الجذور التقريبية لا يعني أن هذه الطريقة العددية التي تم استخدامها لإيجاد الجذر دقيقة مئة في المئة حيث أنه قد تم تقريب النتائج الحسابية في الأمثلة السابقة لأربعة وثمانية أرقام عشرية بعد الفاصلة